2012
DOI: 10.1186/1687-1499-2012-113
|View full text |Cite
|
Sign up to set email alerts
|

A SIMO one-bit time reversal for UWB communication systems

Abstract: With the one-bit time reversal ultra wideband (OTR-UWB) transceiver, the data symbols are encoded using the reversed order of the channel phase. The major factor limiting SISO OTR capacity and performance is intersymbol interference (ISI). As the data rate goes up, the ISI becomes more severe and it degrades system performance and capacity. In this article, a new single input multiple output (SIMO) system is proposed for an OTR-UWB system. The proposed transceiver structure is based on spatial focusing propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Pioneer works of Paulraj et al have namely shown that the richer the scattering environment, the better the time and focusing gains [12]. In UWB systems for instance, TR is suitable as a simple and efficient prefiltering technique for pulse amplitude modulation [13][14][15] since it is realized over large frequency bandwidths. For systems addressing narrower bandwidths and hereby playing with less rich propagation conditions, the so-called rate back-off or oversampling strategies can be used to compensate for some focusing gain degradation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Pioneer works of Paulraj et al have namely shown that the richer the scattering environment, the better the time and focusing gains [12]. In UWB systems for instance, TR is suitable as a simple and efficient prefiltering technique for pulse amplitude modulation [13][14][15] since it is realized over large frequency bandwidths. For systems addressing narrower bandwidths and hereby playing with less rich propagation conditions, the so-called rate back-off or oversampling strategies can be used to compensate for some focusing gain degradation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly experimented in acoustics and ultrasound domains [7] [8] [9], Time Reversal (TR) has also received attention recently for wireless communications [10] [11] [12]. Owing to its inherent time and spatial focusing properties, TR is now studied as a solution for future green wireless communications [12].…”
Section: Some Interesting Researches [1] [2]mentioning
confidence: 99%
“…The effect of quantization error on the UWB transmit beamforming has been investigated to some extent by a few researchers [19][20][21]. They particularly study the TR beamforming performance when only the temporal phase information of the channel impulse response (the sign of each path gain) is provided on the transmitter side, a technique known as one-bit TR [19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…They particularly study the TR beamforming performance when only the temporal phase information of the channel impulse response (the sign of each path gain) is provided on the transmitter side, a technique known as one-bit TR [19][20][21][22][23][24][25]. The majority of these works are theoretical studies based on simplified models which do not consider important propagation phenomena like the frequency dependence of the MPC and path loss exponent [19][20][21]. For example in [19], Chang et al theoretically predict the performance of one-bit TR compared to the conventional TR technique, assuming a Rayleigh fading model holds for UWB channels.…”
mentioning
confidence: 99%
See 1 more Smart Citation